A murine Ig light chain transgene reveals IGKV3 gene contributions to anti-collagen types IV and II specificities. (November 2017) - Clark, Amy G.; Worni-Schudel, Inge M.; Korte, Francesca M.; Foster, Mary H.
Highlights: IGKV3-encoded light chains are prominent among murine anti-type II and anti-type IV collagen autoantibodies. Mice bearing an IGKV3 light chain transgene develop subsets of B cells reactive with each collagen. IGKV3 subgroup genes contribute structural fitness to diverse anti-collagen responses. IGKV3-encoded B cells are regulated in vivo. Abstract: A subset of autoimmune diseases result from autoantibodies targeting epitopes on matrix collagen. The most extensively studied are anti-glomerular basement membrane glomerulonephritis (or its systemic counterpart Goodpasture's disease) that destroys kidneys and lungs, and rheumatoid arthritis that leads to disabling arthritis. Autoantibodies in these disorders bind evolutionarily conserved conformational epitopes on the noncollagenous domain 1 (NC1) of the alpha3 chain of type IV [alpha3(IV)NC1] collagen in glomerular and alveolar basement membranes, and on native or citrullinated type II collagen (CII) in joint cartilage, respectively. The genetic origins of pathogenic anti-collagen B cells in these diseases is unknown, but observations from murine models raise the possibility that they overlap despite distinct in vivo immunopathologies. Monoclonal autoantibodies isolated from mice immunized with alpha3(IV)NC1 collagen or CII show a biased use of Ig light chains (LC) encoded by genes of the IGKV3 subgroup (previously Vk21 family), paired with diverse Ig heavy chains. To further explore this relationship and determine if a single murine IGKV3 LC independently predisposes to both anti-collagen responses, we generated a novel transgenic (Tg) C57BL/6 mouse that expresses a productively rearranged IGKV3-encoded LC, termed mLCV3-Tg, in conjunction with endogenously rearranged Ig heavy chains. Tg mice are also genetically deficient in endogenous kappa chains to permit tracking of the mLCV3 transgene. We show that mLCV3-Tg mice are susceptible to humoral autoimmunity against both collagen chains. Anti-alpha3(IV)NC1 collagen, but not anti-CII, mLCV3-encoded Ig are detected in serum of unmanipulated Tg mice, while Toll-like receptor ligands induce secretion of mLCV3-Tg autoantibodies of both collagen specificities from splenocytes ex vivo. This indicates developmental survival of mLCV3-Tg B cells reactive with each antigen, and is consistent with production of the two anti-collagen autoIg from distinct B cell populations. Reduced B cell numbers, low serum Ig kappa levels, low cell surface Ig kappa density, and abundant endogenous lambda chain expression suggest that subsets of IGKV3-encoded B cells are regulated in vivo by mechanisms that include deletion, anergy, and LC editing. These results support the notion that murine IGKV3 LCs contribute structural fitness to antigen binding sites that support diverse anti-collagen autoimmune responses, that these responses are regulated in vivo, and that these cells can nonetheless readily escape immune regulation.